Hubungan Motivasi Belajar Dengan Hasil Belajar Materi Hukum Newton Kelas VIII SMP Negeri 4 Angkola Selatan Tahun Pelajaran 2022/2023 - Romaito Harahap; Eni Sumanti Nasution; Kasmawati (Universitas Gara Nusantara Padangsidimpuan, 2023)
This study aims to determine whether there is a relationship between learning motivation and learning outcomes of Newton's Law material in class VIII at SMP Negeri 4 Angkola Selatan. . The sample of this research was class VIII students of SMP Negeri 4 Angkola Selatan with a sample size of 30 people. This type of research is correlation research. The analysis technique uses the product moment correlation value. The conclusions from this study concluded that the results of the analysis were based on the results of statistical calculations, namely the relationship between student motivation and learning outcomes in Newton's law material at SMP Negeri 4 Angkola Selatan. Judging from the value of the t test where 0.573 is greater than 2.052.